2015
DOI: 10.1111/anae.13222
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of chest compression feedback during cardiopulmonary resuscitation in lateral tilted and semirecumbent positions: a randomised controlled simulation study

Abstract: SummaryFeedback devices have been shown to improve the quality of chest compression during cardiopulmonary resuscitation for patients in the supine position, but no studies have reported the effects of feedback devices on chest compression when the chest is tilted. Basic life support-trained providers were randomly assigned to administer chest compressions to a manikin in the supine, 30°left lateral tilt and 30°semirecumbent positions, with or without the aid of a feedback device incorporated into a smartphone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
5
0
2
Order By: Relevance
“…One week of situational simulation training and two weeks of practice training has a positive impact on the consolidation and maintenance of knowledge in BLS, AED, and ALS, showing that frequent refreshers at short intervals improve not only skills but also confidence. The results of this study are consistent with those of other researchers [ 33 , 34 ]. The effects of using a knowledge simulation model cannot be ignored, and the results suggest that in future research on emergency knowledge training, training of knowledge and skills is an indispensable component.…”
Section: Discussionsupporting
confidence: 94%
“…One week of situational simulation training and two weeks of practice training has a positive impact on the consolidation and maintenance of knowledge in BLS, AED, and ALS, showing that frequent refreshers at short intervals improve not only skills but also confidence. The results of this study are consistent with those of other researchers [ 33 , 34 ]. The effects of using a knowledge simulation model cannot be ignored, and the results suggest that in future research on emergency knowledge training, training of knowledge and skills is an indispensable component.…”
Section: Discussionsupporting
confidence: 94%
“…These devices range from those that provide simple audio cues to help with the frequency of compressions to very complex devices that assess and record results (Wee et al, 2014). The literature shows some evidence that these devices may increase CPR effectiveness in clinical settings (Yeung et al, 2009; Lukas et al, 2011; Song et al, 2015). Recently, real-time audiovisual feedback has advanced CPR training.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Song Y published a simulation study in 2015 for evaluating the effectiveness of chest compression feedback during CPR in lateral tilted and semi-recumbent positions and found that feedback device improves the application of chest compressions when the chest is tilted. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%